Elaboración y aplicación de un manual que favorezca las relaciones de convivencia institucional de la escuela fiscal “Aquiles Pérez Tamayo” de la comunidad el rodeo, parroquia Chugchilan, del cantón Sigchos, provincia de Cotopaxi, en el año lectivo 2012 – 2013 - Méndez Puente, Edison Patricio (2015)
In The public school “Aquiles Pérez de Tamayo”, located on Rodeo Community, Sigchos town, Cotopaxi Province, check verify mention Educational Institution that there isn´n a manual so it can´t help the interpersonal relatonships, for that reasson it is important to aply the doccument. The imain research was realized through an experimental desing, using the inductive an the deductive method through some instruments such as the survey and the interview, takenin a count that the educative institution contributed in the development of the investigative work....